Chronic pesticide exposure induced aberrant Notch signalling along the visual pathway in a murine model. (1st August 2021) - Sanyal, Shalini; Law, Sujata
Abstract: Pesticides aid in crop-protection against pests and increase yield. However, the xenobiotic stress exerted by pesticides leads to the deterioration of human and animal health. There is a lacuna in our knowledge about their impact on the ocular surface The present work sheds light on this gap by analysing the deterioration of visual acuity as a consequence of pesticide induced xenobiotic stress and Notch pathway dysregulation. Alteration in the expression of vital components of the notch signalling was analyzed along the visual pathway with special focus on its two terminals-the cornea and the visual cortex, by mimicking the on-field scenario regarding chronic pesticide exposure in experimental murine model (Swiss albino mice; Mus musculus ). Various aspects were taken into consideration through visual acuity tests, histological evaluations, culture analyses, wound healing assays, flowcytometric evaluation, fluorescence microscopic studies etc. Complete dysregulation of key players of the Notch signalling pathway was observed in both: cells of the ocular surface as well as those in the murine visual cortex post pesticide exposure, indicating activities relating to cell proliferation, differentiation and wound healing in the pesticide exposed samples. Ultra-microscopic analyses corroborated our findings by revealing the loss of fine neural processes in the visual cortex of the pesticide exposed murine samples, thereby hinting at delayed perception to visual stimuli. In vivo evaluations of the functional capacity of the neuroanatomical structures along the visual pathway also confirmed that pesticide exposure leads to severe damage along the various parts of the visual pathway, right from the ocular surface to the visual cortex. Graphical abstract: Image 1 Highlights: Xenobiotic stress from pesticides deteriorates visual acuity. In vivo evaluations of the functional visual-neuroanatomical capacity. Major points along visual pathway analyzed-cornea, optic nerve and visual cortex. Fine neural process loss observed on ultra-microscopic analyses. Notch dysregulation along the visual pathway-cornea, optic nerve & visual cortex. Abstract : Pesticides are the commonest solution for controlling pests in developing nations, however the economic benefits from the increased crop-yield by pesticide usage come at the cost of health. This article analyses the deterioration of visual acuity incurred as a consequence of the xenobiotic stress exerted by pesticides and sheds light on the dysregulation of Notch signalling by evaluating its key molecules along the visual pathway with special focus on its two terminals-the cornea and the visual cortex.